COMPARISON OF TWO DIAGNOSTIC IMAGING TECHNIQUES FOR DIAGNOSISNG SYNOVIAL CHONDROMATOSIS OF THE TEMPOROMANDIBULAR JOINT - Shahpaska, Budima Pejkovska; Rusevska, Biljana; Markovska-Arsovska, Mirjana; Nikolovski, Bruno; Zlatanovska, Katerina; Zarkova-Atanasova, Julija; Kovacevska, Ivona; Sylejmani, Mimoza; Pejkovska, Ana; Jancheska Georgievska, Tatjana (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Asymptomatic pathological formations sometimes can be revealed, when patients come to treat other dental issues such as caries or periodontal problems. The paraclinical diagnosis of synovial chondromatosis is a very rare finding, which is why the right diagnostic criteria are needed. To represent a paraclinical finding of synovial chonromatosis of the temporomandibular joint in a patient. A 42-year old patient with severe periodontal changes came to the University Dental Clinical Centre “St. Panteleimon”-Skopje, searching for a prosthetic rehabilitation. After anamnesis was taken, clinical extraoral and intraoral examinations were performed, paraclinical analysis were needed. After receiving the ortopantomographic image, a team of dental specialists have realized the presence of a pathological formation without definitive diagnosis. A computer tomography was performed, for definitive differential diagnosis. Oftentimes patients visit the dentists when they have aesthetic issues. When detailed analysis are needed, it is sometimes rare to discover changes such as synovial chondromatosis. Literature data has confirmed our finding that this condition is often discovered by chance, because of the lack of symptomatology when other analysis are performed. That is why ortopantomography should be followed by computer tomography. Once the diagnose for synovial chondromatosis is formed, the surgeons decide whether to surgically remove or follow the changes in the temporomandibular joint.The imaging techniques are of crucial importance to help the final diagnosis of pathological changes in the temporomandibular joint. Key words : synovial chonromatosis, lack of symptoms, paraclinical examinations, computer tomography.